Climate change and sustainable economy in multipurpose maritime port concessions, Peru - Coayla, Edelina; Trancón, Imelda; Bedón, Ysabel; Romero, Violeta (Frontiers in Sustainability, 2025)
The greening of concession ports is relevant for sustainability. This study aims to analyze the nexus between climate change and the sustainable economy of Peru’s maritime port concessions. In the period 2011–2023, the cargo in metric tons mobilized by the multipurpose maritime terminals was characterized for the high containerized cargo through the Muelle Norte APMT (Callao), mostly in unloading operations, although by the Salaverry terminal, no containerized cargo was mobilized; the Matarani port terminal increased its shipping operations mainly copper solid bulks, since 2016. Reflective, correlation and regression methods were used; the indicator of climate change included the average sea level. We found a negative correlation between sea level rise and total cargo traffic of the Muelle Norte APMT concession (2011–2023). The regression analysis revealed a significant positive impact of investment on total cargo traffic through multipurpose ports, while also confirming the negative influence of sea level rise on cargo traffic, which is an indicator of a sustainable economy. We conclude that adaptation to climate change requires investment in port infrastructure in the face of sea level rise and conversion to green smart ports that contribute to SDGs 9 and 14 on innovation and infrastructure, and ocean and marine ecosystem conservation.